2022
DOI: 10.1007/s11187-022-00629-2
|View full text |Cite
|
Sign up to set email alerts
|

A contingency model of employees’ turnover intent in young ventures

Abstract: A defining characteristic of young ventures is that they are more likely to experience periods of change (of both a positive and negative nature) than are established organizations. This could result in a misalignment between employees’ expectations when hired and actual work experiences. Based on met expectations theory, we argue that employees’ experiences in young ventures result in greater turnover intent over time. We further theorize that the relationship between time and turnover intent is contingent on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…Recent advancements in machine learning () have opened up new opportunities for predicting employee turnover. Studies have demonstrated the efficacy of machine learning algorithms such as logistic regression, decision trees, and support vector machines in predicting turnover intentions based on diverse sets of predictors (Lazzari et al, 2022;Domurath et al, 2023). For instance, Lazzari et al (2022) compared various classification models and found logistic regression and LightGBM to be the top-performing algorithms for predicting turnover intentions.…”
Section: Machine Learning Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent advancements in machine learning () have opened up new opportunities for predicting employee turnover. Studies have demonstrated the efficacy of machine learning algorithms such as logistic regression, decision trees, and support vector machines in predicting turnover intentions based on diverse sets of predictors (Lazzari et al, 2022;Domurath et al, 2023). For instance, Lazzari et al (2022) compared various classification models and found logistic regression and LightGBM to be the top-performing algorithms for predicting turnover intentions.…”
Section: Machine Learning Modelsmentioning
confidence: 99%
“…For instance, Lazzari et al (2022) compared various classification models and found logistic regression and LightGBM to be the top-performing algorithms for predicting turnover intentions. Similarly, Domurath et al (2023) developed a contingency model of turnover intent in young ventures using longitudinal data and highlighted the predictive power of machine learning in understanding turnover dynamics in entrepreneurial firms. Moreover, the literature on employee turnover provides valuable insights into the determinants, consequences, and predictive models of turnover.…”
Section: Machine Learning Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore desirable not only to define a suitable applicant profile in terms of the position to be filled, but also to assess the risk of the applicant quitting his or her job. According to Domurath et al (2023), the desire to change jobs grows stronger over time, and this effect is particularly strong for employees working in low-growth ventures. Moreover, people under the age of 30 often change their jobs as they are still figuring out what they want to do in life (Arnett, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore desirable not only to define a suitable applicant profile in terms of the position to be filled, but also to assess the risk of the applicant quitting his or her job. According to Domurath et al (2023), the desire to change jobs grows stronger over time, and this effect is particularly strong for employees working in low-growth ventures. Moreover, people under the age of 30 often change their jobs as they are still figuring out what they want to do in life (Arnett, 2006).…”
Section: Introductionmentioning
confidence: 99%